2023
DOI: 10.1002/pssa.202200762
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Strengthening of Dislocation and Heterodeformation Induced in Gradient Nanograined Copper Film: A Molecular Dynamics Study

Abstract: Unlike conventional homogeneous nanograined (NG) materials, gradient structured materials combine high strength and ductility. The gradient nanograined (GNG) structures are divided into three zones by grain size: the small‐grained zone, the transition‐grained zone, and the large‐grained zone. Molecular dynamics (MD) simulation is performed to investigate the effect of the widths of zones on the strength of GNG structures with different grain sizes. The simulation results reveal the strengthening mechanism of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This transforms the O‐R‐O structure's original unidirectional gradient distribution of “small grains‐large grains‐small grains” to a multidirectional gradient distribution consisting of alternating small and large grains, which increases the strain strength gradient in the material's plastic deformation, further strengthening the HDI effect. [ 50,51 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This transforms the O‐R‐O structure's original unidirectional gradient distribution of “small grains‐large grains‐small grains” to a multidirectional gradient distribution consisting of alternating small and large grains, which increases the strain strength gradient in the material's plastic deformation, further strengthening the HDI effect. [ 50,51 ]…”
Section: Resultsmentioning
confidence: 99%
“…This transforms the O-R-O structure's original unidirectional gradient distribution of "small grains-large grains-small grains" to a multidirectional gradient distribution consisting of alternating small and large grains, which increases the strain strength gradient in the material's plastic deformation, further strengthening the HDI effect. [50,51] The GNG structure creates synergy between various strengthening mechanisms, from where HDI strengthening is dominant. According to the modified rule of mixtures (ROM) [50,52] σ Where σ Y is the yield strength of the whole sample, and Δσ is the HDI strengthening contribution.…”
Section: Strengthening Of Gradient Nano-grained (Gng) Structurementioning
confidence: 99%
“…where T m is the melt temperature of the material. ∆G is the activation energy for dislocation and precipitate interaction [56][57][58].…”
Section: Numerical Modelmentioning
confidence: 99%
“…Wu et al 3 and Cheng et al 12 attribute the additional strain hardening of GNG metals to the storage of geometrically necessary dislocations near grain boundaries or within grains caused by the grain gradient size distribution, which also makes the material highly ductile. Qiang et al 13 revealed the strengthening mechanism of the GNG model structure by varying the width of the region for each grain size, showing that the change in grain size leads to a shift in the deformation mechanism from grain boundary motion of small grains to dislocation slip of large grains, and at the same time realizes the synergistic strengthening of dislocations and heterogeneous structural deformation in the GNG structure. Cheng et al 14 established the mechanism linking the structural gradient, plastic strain gradient, extra back-stress and extra strength in GNG Cu through experiments and modeling, and explained the higher extra strength and work-hardening of GNG metal based on the extra back stress induced by GND buildup.…”
Section: Introductionmentioning
confidence: 99%